MAKNA SIMBOLIS DAN FUNGSI TARI HUDOQ SUKU DAYAK WEHEA DI PEDALAMAN KALIMANTAN TIMUR - Paulus Wilfridus Gobang (Jurnal Komunikasi dan Budaya, 2022)
Hudoq dance is included in the type of traditional folk dance, because it was created by the local community of the Dayak Wehea tribe in the interior of East Kalimantan. Hudoq dance is performed once a year after the rice harvest. Hudoq dance serves as an expression of gratitude for the success of the harvest and protection from supernatural spirits for the village and the community. This article aims to find out the symbolic meaning and role of the Hudoq dance of the Dayak Wehea tribe in the interior of East Kalimantan. The method used in this study is literature via the internet. Through this study it can be concluded that the symbolic meaning of the Hudoq dance of the Dayak Wehea tribe, namely the Hudoq mask resembles a wild animal which is dominated by red, black and white as the favorite colors of the gods while the motifs on the Hudoq mask are typical carvings of the Dayak Wehea tribe. The red color on the Hudoq mask symbolizes courage in people's lives and the black color is believed to be a form of majesty while the white color is a symbol of purity. The symbolic meaning of the Hudoq dance in Lom Plai (harvest thanksgiving) can be seen from the function of the dance and the elements of its presentation. The role of the Hudoq dance is as an expression of gratitude for the success of the harvest during the year and also as a tribute to the ancestral spirits who have protected the residents and the village. This is intended as a form of appreciation to their predecessors that the Dayak Wehea community continues to preserve customs, so the Lom Plai event is held every year.